Diseño e implementación de un banco de pruebas para construcción y estudios de circuitos neumáticos - Merino Rojas, Jefferson Mauricio (2023)
This project focuses on the design and implementation of a test bench for the construction and study of pneumatic circuits. Ergonomic parameters based on the female 5th percentile were considered, with the objective that the bench can be used by 95% of the Ecuadorian Latin American population according to the NTE INEN-ISO 11226 standard. In addition, the selection of materials was taken into account, with a focus on carbon steel, complying with ASTM A36 and AWS standards for welding. On the other hand, the design process began with an analysis of existing prototypes in the market regarding pneumatic didactic benches, choosing the most suitable for the learning conditions. Then, the structure was modeled using CAE software, where a stress analysis was performed with respect to three structural profiles, concluding that the 30x30 mm profile offers good safety parameters and low cost. Additionally, a vibration analysis was performed to determine the natural frequencies of the structure to avoid resonance with respect to the frequency emanating from the compressor. Once these parameters were determined, the didactic bench was built following the work plan elaborated in the Autodesk Inventor software, taking into account the work safety parameters, obtaining a reliable and durable final product. The user manual was created with the purpose of providing clear and useful instructions for students, enabling them to get the most out of the test stand. It includes detailed information on safety, risk factors present on the bench, preventive measures to be carried out to prevent accidents and the corresponding maintenance with respect to the components for pneumatic systems. The practical guides were developed with the objective of enabling students to better understand the operation of pneumatic systems. To validate their effectiveness, a survey related to the didactic bench and the respective guides was conducted. In this survey, students selected the most accepted option based on each question and practical guide provided. Subsequently, the data collected were tabulated using Excel software, thus allowing the calculation of a percentage of satisfaction in relation to the pneumatic didactic bench. Keywords: Didactic bench, pneumatic systems, user's manual, material selection.